O regime de colaboração entre os órgãos normatizadores da educação brasileira - Grossi Junior, Geraldo (2011)
This Master-Degree dissertation is tied to the line Search “Movimentos Sociais, Política e Educação Popular” and reflects on attempts to implement the collaboration, promoted by regulatory agencies of the Brazilian Education. Begins with a historical account about the process of centralization and decentralization experienced by the Brazilian Education since the time of Empire to the presents days, including the specification of actions developed by the State Boards of Education in search for Development and implementation of the scheme Collaboration between education and the vision for this coming theme of the current presidents of State Boards of Education in the states of Amazonas, Paraná and Piauí. Are given the difficulties encountered in that establish a framework for collaboration. In this perspective, research has taken the right approach to character qualitative, descriptive and analytical, that involves literature review and documentary, using semi-structured. Seeks to understand why, even in the Constitution and Federal Law of Directives and Bases of Education, the Scheme Collaboration hasn’t yet structured in the Brazil’s education system. Is able to notice the lack of clarity about what would be the regime's collaboration and about which possible practices could be embraced by their deployment, which was prevented to be operationalized. Also can sees that the expectation on the promulgation of Law complementary to the Constitution and to regulate the LDB Collaboration Scheme has provided agencies normative systems of a certain lethargy. The few experiences developed in order to provide shares the effective exercise of the concrete scheme Collaboration yet, they are numerically small and incipient. Add this complexity to create the System National Education mentioned in Amendment Constitutional 59/09. It can be concluded that still makes necessary to expand the debate in order to find the clarity of the meaning of the theme, as well as its forms application.